IMPLEMENTASI MANAJEMEN KEARSIPAN DI SD ISLAM ABAIS - Sabrina, Asa; Rahmawati, Devi; Indah, Munita; Salma, Putri Alya (STKIP Pesisir Selatan, 2025)
This study aims to analyze the implementation of archives management at ABAIS Islamic Elementary School by highlighting the planning, organizing, implementing, and monitoring functions to identify operational constraints and formulate technology-based solutions. This research method uses a descriptive qualitative approach through in-depth interviews with archivists, participant observation, and documentation analysis. Data were analyzed through reduction, presentation, and conclusion drawing, with data validity tested through triangulation of sources and methods. The findings indicate that the archive creation process is carried out in a hybrid manner, combining manual and digital procedures for archives of letters, student data, and financial documents. However, archive storage is still mixed between active and inactive archives, lacks an indexing system, and is only organized chronologically, thus slowing retrieval. An archive reduction mechanism has not been implemented due to limited human resources and the age of the institution. Supporting factors include leadership commitment, while inhibiting factors include minimal infrastructure and staff discipline in data input. This study offers an archiving improvement model that combines archiving SOPs, a hybrid physical-digital system, SIKD-based digitization, and the preparation of a structured retention schedule a combination rarely discussed in archiving studies at the Islamic elementary school level.